Aplicación de proceso contable en tendencias de Moda Com, del cantón Yanzatza, periodo: octubre – diciembre / 2014 - Agreda Gaona, Andreina Esperanza (2015)
APPLICATION OF ACCOUNTING PROCESS IN FASHION TRENDS COM, YANZATZA CANTON, PERIOD OCTOBER - DECEMBER 2014, in order to achieve the economic benefit of the warehouse, and the present work is structured according to the requirements and regulations of the National University of Loja, Distance Learning mode for obtaining degree in Accounting and Auditing Accountant CPA Auditor CPA. The collection of documents allowed to organize information, based on this initial inventory, baseline status was obtained; according to the needs of the store the chart of accounts, user account was created, the main and auxiliary books were designed by obtaining the trial balance, worksheet and financial statements, in accordance with the provisions of International Accounting Standards and Ecuadorian, thus fulfilling the objectives. With the results obtained after completion of the research process were concluded: that implementing an accounting system in stock is optimal tool that has a manager to make the right decisions with real financial statements so it is recommended to continue with the application of multiple account accounting system, which will be an effective tool for organizing the company accounting